Examining the Effects of Core Stabilization Exercises and Myofascial Release Technique in Individuals with Chronic Neck Pain: A Randomized Clinical Trial - Dalakci, Muhammed Samed; Ozudogru, Anil; Alkan, Halil (Springer Heidelberg, 2026)
Background Core Stabilization Exercises (CSE) and myofascial release therapy (MRT) are commonly used methods for musculoskeletal pain. The combined use of these two methods may provide long-term and sustained relief or reduction of pain in both deep and superficial tissues. Objective This study aimed to evaluate the effects of MRT using a roller combined with CSE in adults with chronic neck pain (CNP). Methods A total of 58 participants were initially enrolled and randomly divided into 2 groups. Thirteen participants dropped out during the intervention period, leaving forty-five participants whose data were included in the analyses. The CSE program was applied to participants in the CSE group 3 days per week for 6 weeks. In addition to CSE, MRT with a roller massager was performed 3 days per week for 6 weeks for participants in the CSE + MRT group. Results In the CSE + MRT group, functionality increased significantly (p < 0.001). The increase in lateral-medial dynamic balance was not statistically significant (p = 0.066). Conclusion The combination of CSE and MRT is more effective than CSE alone in increasing the pressure pain threshold and reducing pain in individuals with CNP.
Keywords: Chronic Neck Pain; Core Stabilization Exercises; Myofascial Release Therapy; Fascia